On the Passage of a Relativistic Spinless Particle through a Potential Barrier - Karapetyan, G. G.
Contradictory descriptions of the passage of a relativistic particle through a high potential barrier are investigated. The conventional energy-momentum relation yields a real momentum for the particle within the barrier, suggesting classical particle motion. However, this contradicts the law of conservation of energy, which necessitates that the particle's momentum be imaginary, thereby rendering classical motion impossible. This paradox is resolved through the adoption of a novel energy-momentum relation.
Keywords: Physics